Microwave-assisted synthesis of novel nanostructured Zn3(OH)2V2O7·2H2O and Zn2V2O7 as electrode materials for supercapacitors. (17th November 2017) - Li, Yingdi; Teng, Yifei; Zhang, Ziqing; Feng, Yi; Xue, Peng; Tong, Wenming; Liu, Xiaoyang
Abstract : Zn3 (OH)2 V2 O7 ·2H2 O nanowires and nanowire-shaped Zn2 V2 O7 synthesized through a microwave-assisted method and a successive annealing exhibited outstanding electrochemical performance. Abstract : In recent years, ternary metal oxides with their multiple oxidation states and unique morphologies have attracted widespread attention as a result of their potential applications in the electrochemical energy storage field. However, there are few reports about the energy storage capacity of metal vanadate, and no efficient and environmentally friendly synthesis methods have been reported so far. In our work, Zn3 (OH)2 V2 O7 ·2H2 O nanowires were successfully synthesized through a facile, rapid, and green microwave-assisted hydrothermal method at 100 °C for 50 min, and tightly connected Zn2 V2 O7 elliptical nanoparticles were acquired by a subsequent calcination process at 400 °C for 1 h. With a series of structural and morphological characterization techniques, we found that the surfactant glycine played a key role in controlling the composition and morphologies during the synthesis process: adding 0.15 M glycine to the mixed solution was identified to be the appropriate condition through a series of studies. More importantly, the as-synthesized Zn2 V2 O7 electrode exhibited a superior specific capacitance of 427.7 F g −1 (at 1 mA cm −2 ) and enhanced cycling performance, with 83.71% capacitance retained after 1000 cycles. Additionally, the Zn2 V2 O7 /Ni-foam//AC ASC device displayed an energy density of 18.7 W h kg −1 at a power density of 272.7 W kg −1 . The Zn3 (OH)2 V2 O7 ·2H2 O nanowires and Zn2 V2 O7 elliptical nanoparticles synthesized under microwave-assisted conditions were used as electrode materials in supercapacitors for the first time, which paved the way for zinc vanadate's application in the energy storage field.